The Role of Morality and Ethics in Utilizing Artificial Intelligence for Technology and Vocational Education in the Digital Era of Industry 4.0 - Muhammad Sadam Rizkylillah; Rafida Sahartaqiya; Aghnina Camilla Husna; Suyitno Muslim; Wisnu Djatmiko (Proceeding of the International Conferences on Engineering Sciences, 2024)
The digital era in the industrial revolution 4.0 has brought significant changes in various aspects of life, including education. With the presence of increasingly sophisticated digital technology and the widespread use of Artificial Intelligence (AI), the education system is currently faced with new challenges to adapt to the times. However, the emergence of AI also has a negative impact on education, especially in the context of Technology and Vocational Education, namely increasing plagiarism, excessive dependence, lack of skill development, and weakening of culture, norms, and interactions between students and lecturers. This study aims to analyze the moral and ethical role in the use of AI in Technology and Vocational Education. The literature review research method is used in this study with a qualitative approach. Secondary data collection was carried out with the help of Google Scholar web technology and the bibliometric processing application VOSViewer. The data analysis technique applies the Miles & Hubberman model which consists of: data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that morals and ethics play a central role in the utilization of artificial intelligence (AI) in Technology and Vocational Education in the digital era of the Industrial Revolution 4.0. The study also recommends strategic steps to ensure the use of AI in Technology and Vocational Education remains ethical and effective.